B10 cells decrease fibrosis progression following cardiac injury partially by IL‐10 production and regulating hyaluronan secretion. Issue 2 (19th May 2021) - Chen, Rong; Liu, Fang; Xia, Lin; Che, Nan; Tian, Yu; Cao, Yuwen; Zhang, Shiqing; Xu, Huaxi; Su, Zhaoliang
Abstract: B10 cells play negative roles in inflammatory disorders by producing IL‐10. However, their effects on fibrosis have not been elucidated. Therefore, this study was conducted to examine the dynamic changes of B10 cell frequency and their potential role in cardiac fibrosis. We found that the frequency of B10 cells was significantly increased, and they participated in the regression of fibrosis via IL‐10, particularly by accelerating hyaluronan secretion and inhibiting collagen deposition. In vivo, hyaluronan ablation or treatment significantly restricted cardiac fibrosis development. hyaluronan‐induced conversion of M1/M2 Mc was dependent on the size of hyaluronan. Low molecular weight hyaluronan promoted the conversion to M1 Mϕ, whereas medium and high molecular weight hyaluronan accelerated Mϕ transdifferentiation into the M2 phenotype. Adoptive transfer of B10 cells significantly attenuated collagen deposition whereas CD19 −/− mice with reduced B10 cells exacerbated fibrosis following cardiac injury. Our results provide new evidence suggesting that B10 cells exert antifibrotic effects by regulating the extracellular matrix composition during cardiac injury, and also highlight that B10 cells may serve as a promising therapeutic candidate for managing cardiac fibrosis‐associated disorders. Graphical Abstract: B10 cells benefit cardiac scar‐free repair following cardiac injury partially by IL‐10 production and regulating hyaluronan secretion.